2002
DOI: 10.1097/00003246-200211000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of off-pump coronary surgery on the mechanics of the respiratory system, lung, and chest wall: Comparison with extracorporeal circulation

Abstract: Coronary bypass surgery with and without extracorporeal circulation results in dramatic impairment of respiratory system mechanics. Based on respiratory system mechanics, early extubation after coronary artery bypass grafting should be performed with caution, no matter whether the off-pump or cardiopulmonary bypass technique is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
1
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
1
26
1
3
Order By: Relevance
“…In other observational studies and randomized trials [2,11,17-21,30,31], however, authors found off-pump versus on-pump coronary artery surgery to be associated with less pulmonary complications, less oxygenation impairment, earlier extubation, shorter mechanical ventilation and less often pneumonia, but these observations also remained largely unexplained. In contrast, other authors reported no differences in lung mechanical changes, but this is controversial too [5,6,11,23,29,30]. Our results finally do not agree with the suggestion that off-pump surgery is associated with less radiographic atelectasis than on-pump surgery [32], which, otherwise, was not confirmed in other studies [11,29].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In other observational studies and randomized trials [2,11,17-21,30,31], however, authors found off-pump versus on-pump coronary artery surgery to be associated with less pulmonary complications, less oxygenation impairment, earlier extubation, shorter mechanical ventilation and less often pneumonia, but these observations also remained largely unexplained. In contrast, other authors reported no differences in lung mechanical changes, but this is controversial too [5,6,11,23,29,30]. Our results finally do not agree with the suggestion that off-pump surgery is associated with less radiographic atelectasis than on-pump surgery [32], which, otherwise, was not confirmed in other studies [11,29].…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, a lung vascular injury and oedema may be associated with deteriorated gas exchange and pulmonary compliance after surgery, although this is controversial [2,3,5-7]. We do not know whether the transfusion of RBC concentrates was a marker or a mediator of severe lung vascular injury and a high PLI, as in TRALI [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with coexisting chronic obstructive airway disease derive better early clinical benefit from CABG performed without CPB compared with on-pump surgery [47], although in low-risk patients, OPCAB induces impairment of the mechanics of the respiratory system, lung and chest wall similar to on-pump CABG [48].…”
Section: High Risk Surgical Patientsmentioning
confidence: 99%
“…19,20 But Fransen et al, 21 had observed that the acute phase response of systemic inflammation in CABG patients, which was historically been ascribed to CPB is predominantly caused by surgical procedure per se and both OPCABG and conventional CABG produces similar degrees of oxidative injury. 4,5,22 Oxidative stress results from an imbalance between local antioxidant defences and formation of reactive oxygen derived free radicals, which are generated and released by activated inflammatory cells. ROS are highly reactive and can induce lipid peroxidation (oxidation of membrane phospholipids) and the accumulation of their products including MDA, 7,16,23,24 4-hydroxy-2-nonenal, acrolein, hydroperoxides 6 and F2-isoprostanes 7,10,14 acts as an indirect measure of free radical activity.…”
Section: Discussionmentioning
confidence: 99%